Poverty and conflict : a review of literature - Ganepola, Varuni; Thalayasingam, Prashan; Centre for Poverty Analysis (Sri Lanka) (Colombo : Centre for Poverty Analysis, 2004)
Evaluation of research on interrelationship of poverty and social conflict in Sri Lanka.
Keywords: Poverty -- Research -- Sri Lanka; Social conflict -- Evaluation -- Sri Lanka